THE EFFECT OF STUDENTS’ LEANING STYLE AND SELF-CONCEPT TOWARD MATHEMATICAL CREATIVE THINKING ABILITY IN LINEAR ALGEBRA SUBJECT - Dian Purwaningsih (MEJ (Mathematics Education Journal), 2017)
The students’ low ability in absorbing the information they got in thelearning activity. Another factor was students’ self-concept which not quitegood. Students’ self-concept can be declared through their selfunderstanding, as well as their self-confidence toward their ability to solvetheir assignment or problem. This study was aimed to investigate the effectof learning style toward the mathematical creative thinking ability, toinvestigate the effect of self-concept toward mathematical creative thinkingability, and to investigate the effect of learning style and self-concept towardmathematical creative thinking ability. This study was one of the ex-postfacto with descriptive approach. Based on the aim of this study, this studyused regression analysis technique in the form of simple analysis regressionand double analysis regression. The result of this study showed that therewas an effect of learning style toward mathematical creative thinking ability,there was an effect of self-concept toward mathematical creative thinkingability, and there was an effect of learning style and self-concept towardmathematical creative thinking ability